Development of a novel shuttle system for the transfer of gonococcal genes between Escherichia coli and Neisseria gonorrhoeae. - Gauthier, Benoit R. (University of Ottawa (Canada), 1990)
The objective of this project was to construct a shuttle vector for the transfer of gonococcal genes between Escherichia coli and Neisseria gonorrhoeae using an in vitro-derived deletion derivative of the penicillinase-producing plasmid of N. gonorrhoeae. The ability of N. gonorrhoeae strain F62 to selectively acquire a 1.5 kb TagI fragment derived from the 4.2 kb cryptic plasmid was confirmed by uptake experiments. Neither the 1.5 kb fragment nor the oligonucleotide had any effect on the ability of chromosomal DNA to transform a strain that did not recognize the 1.5 kb fragment. However, the efficiency of transformation of the strain that did acquire the fragment was lowered by the presence of the two competing DNAs. Conjugation, using pUB307, an IncP conjugative plasmid, was the most efficient method for introducing plasmid DNA into recipient gonococci. Deletion derivatives of pJD8 (smallest deletion derivative of pJD4) were constructed in order to reduce the size of pJD8 to the smallest mobilizable plasmid. Plasmid pGRY4 was chosen as a basis for the construction of a shuttle vector. The lacZ complementation system of E. coli and the xy1E system from Pseudomonas putida were investigated as possible positive selection markers for the shuttle vector. Several problems were encountered when the proC gene of N. gonorrhoeae was cloned into pGCY1. Future transformation attempts should be performed in a restriction$\sp-$ and recA$\sp-$ strain. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.